A TAXONOMIC STUDY OF BALI AND LOMBOK BEGONIA (BEGONIACEAE) - Deden Girmansyah (BRIN Publishing (Penerbit BRIN), 2009)
GIRMANSYAH, DEDEN. 2009. A taxonomic study of Bali and Lombok Begonia(Begoniaceae). Reinwardtia 12(5): 419–434. A taxonomic study of Bali and Lombok Begonia was based on an investigation of morphological characters from 60 specimens in Herbarium Bogoriense.This study shows that there are 8 species that can be recognized: three species already in the genus (Begonia coriacea, B. longifolia, and B. tenuifolia) and five new (Begonia baliensis, B. lempuyangensis, B. pseudomuricata, B. multibracteata, and B. lombokensis).